A Comprehensive Study for Assessing the Demand and Supply Dynamics of Parkinson's Disease Medication in Roorkee, Uttarakhand: Review Article (Journal of Pharma Insights and Research, 2024)
Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by the loss of dopaminergic neurons in the substantia nigra pars compacta region of the midbrain. This depletion of dopamine, a neurotransmitter crucial for regulating movement, leads to the characteristic motor symptoms of PD, including tremors, rigidity, bradykinesia, and postural instability. In India, the prevalence of PD is increasing, necessitating greater attention to the availability and distribution of appropriate medication. This comprehensive study aims to assess the demand and supply dynamics of PD medication in Roorkee, Uttarakhand. After recording the sales per week of various drugs, brands, dosage forms, and strengths available in Roorkee, it was determined that SINEMET (Carbidopa + Levodopa) is widely accessible in the region, with STALEVO, MIRAPEX (Pramipexole), and ARTANE (Trihexyphenidyl) being the other prominent brands available in local medical stores. These medications are primarily in tablet form. Sales data from different stores indicated that SINEMET (Carbidopa + Levodopa 25/250 mg) is the most popular drug in the Roorkee area for treating PD. In terms of drug type analysis, levodopa-based decarboxylase inhibitors, particularly the combination of Levodopa and Carbidopa, currently hold a dominant position in the PD drug market in the region